ChemInform Abstract: Multicomponent Reactions in PEG‐400: Ruthenium‐Catalyzed Synthesis of Substituted Pyrroles. Issue 15 (April 2015) - Chandrasekhar, Srivari; Patro, Vidyavathi; Chavan, Lahu N.; Chegondi, Rambabu; Gree, Rene
Abstract: The eco‐friendly protocol can not be applied to vicinal diols other than ethylene glycol (III), such as butane‐2, 3‐diol, phenylethane‐1, 2‐diol, 1, 2‐diphenylethane‐1, 2‐diol, and cyclohexane‐1, 2‐diol.